Exploring the Impact of eHMI Display Location and Vehicle Type on Pedestrian Perceptions: A VR User Study - Nianzhao Zheng; Jialong Li; Yan Zhang; Kenji Tei (IEEE Access)
External human-machine interfaces (eHMIs) are expected to improve pedestrian interactions with automated vehicles (AVs) and foster greater social acceptance. While earlier research has primarily focused on refining eHMI designs by examining different modalities and color preferences, determining the most effective eHMI location on vehicles remains a significant challenge. Although some studies have started investigating various eHMI display locations, a comprehensive analysis of factors related to vehicle type and eHMI location that affect pedestrian preferences remains insufficient. To address this gap, we conducted a Virtual Reality user study to evaluate pedestrian responses to different AVs equipped with eHMIs positioned in various locations. Our results indicate that pedestrians perceive larger vehicles as less safe, yet the increased visibility provided by longer light bands on these vehicles influences their crossing decisions. Furthermore, the location and height of the eHMI in relation to eye level are critical, as improper positioning can reduce its visibility, leading to a negative impression among participants.